SELECTED GEOSITES FOR GEOHERITAGE, GEOTOURISM, AND GEOCONSERVATION IN SONGKHLA PROVINCE, SOUTHERN THAILAND - Nazaruddin, Dony Adriansyah (Quaestiones Geographicae, 2019)
A systematic investigation has been conducted in several selected geosites in Songkhla Province (Southern Thailand) including inventory, characterization, classification, assessment, and evaluation to study their potentials for geoheritage, geotourism, and geoconservation. A list of geosites have been established for this study, consisting of Songkhla Lagoon/Lake, Samila Beach, Tone Nga Chang (Elephant’s Tusk) Waterfall, Khao Rup Chang (Dragon and Elephant) Cave, and Khao Daeng Hot Spring. Characterization of all these sites have showed that most of the sites have unique and interesting landforms (geomorphological sites), except only a hot spring site (hydrogeological site). The geosites have features of small to large scales (tens meter to larger than 10 km). Qualitative and quantitative assessments have been carried out based on geoheritage values (scientific & educational, aesthetic, recreational, cultural, etc.), with the state/provincial to national levels of significance. Geoconservation efforts should be conducted in all these sites for some purposes, such as research and education as well as geotourism in the province and the region.